Arsenic Trifluoride Sulphor Trioxide Mixtures - Chan Shing-shee, Selwyn (My University, 2024)
A liquid obtained by distillation from mixtures of arsenic trifluoride and sulphur trioxide which was supposed to have the composition 2AsF3,3SO3 has been regarded as a definite chemical compound for which several structures have been proposed. The reaction between arsenic trifluoride and sulphur trioxide has been reinvestigated using F19 n.m.r. spectroscopy, vapour-density measurements and cryoscopy in fluoro sulphuric acid. Evidence has been obtained for the formation of the new compounds AsF2(SO3)F), AsF(SO3F2 and AsF2(SO3F)3, although none of these have been obtained pure. The supposed compound 2AsF3,3SO3 is in fact a constant-boiling mixture which does not have exactly this stoichiometric composition and whose composition varies with the pressure. In mixtures containing an excess of sulphur trioxide polysulphuryl fluorides SnO3n_1F2 are formed in substantial amounts.